Designing A Game On FPGA Using Verilog - Loh, Yi Qhi (2020)
As the rate of technological advancement increases with time, the market of FPGA has grown dramatically and becomes popular among the field of ASIC. Ease of creation and maintenance lead FPGA to become an attractive solution to high speed and efficient applications. From a simple interface circuit to a complex state machine, even to the extent of System on Chip (SOC), the importance of FPGA chips cannot be ignored. Several testings were carried out in this project before the start of specific technical design in order to avoid any unwanted syntax errors and equipment wiring errors. This project mainly focused on the design and implementation of an FPGA-based Ping Pong game, consisting of both the hardware and software design working coherently. For hardware-wise, the host computer was used to program and configure the design; FPGA was implemented for operating the game, and the VGA monitor for display. At the same time, the software part included the design of the overall system, input key module, VGA display module, as well as the game control module. The game design focused on "Double Player Mode", which simulates the real-life ping-pong game. The movement of the paddles was controlled by pressing the push buttons of FPGA. The difficulty level of the game was increased by adding the extra features, which includes the speed control of the ball and the size control of the paddles. The judgment of victory and defeat was done by comparing the accumulated points of the players. If one of the paddles unable to catch the ball and reflect it, the ball will continue to move and touch the up or down borderline of the rectangular frame, then the opponent will earn fifteen points, and the next round began. The game-winner is who first accumulated to 90 points. The game will restart again if the player inputs the RESET key. At the end of the project, the compilation of the game design is found to be successful. The game can be displayed and functioned smoothly without any delay. Thus, this project is considered successful as the objectives were achieved.